Construction of Chiral Bridged Tricyclic Benzopyrans: Enantioselective Catalytic Diels–Alder Reaction and a One‐Pot Reduction/Acid‐Catalyzed Stereoselective Cyclization1. Issue 19 (24th March 2014) - Song, Aiguo; Zhang, Xishuai; Song, Xixi; Chen, Xiaobei; Yu, Chenguang; Huang, He; Li, Hao; Wang, Wei
Abstract An asymmetric two‐step approach to chiral bridged tricyclic benzopyrans, core structures featured in various natural products, is described. In the synthesis, an unprecedented enantioselective catalytic decarboxylative Diels–Alder reaction is developed using readily available coumarin‐3‐carboxylic acids and aldehydes as reactants under mild reaction conditions. Notably, the decarboxylation‐assisted release of the catalyst enables the process to proceed efficiently with high enantio‐ and diastereoselectivity. Furthermore, a one‐pot procedure for either a LiAlH4‐ or NaBH4‐mediated reduction with subsequent acid‐catalyzed intramolecular cyclization of the Diels–Alder adducts was identified for the efficient formation of the chiral bridged tricyclic benzopyrans.